The family physician as patient advocate: a case report of a patient with endocarditis (Portuguese Journal of Family Medicine and General Practice, 2016)
Introduction: Although endocarditis caused by Borrelia burgdorferi is rare, this case report is relevant because it stimulates reflection on the core competencies of the family physician. Case report: A 36 year-old male patient with a history of arterial hypertension and cardiac surgery in adolescence for repair of an interventricular communication, presented with a four-month history of vertigo, hemianopsia, headache, memory loss, hemiparesis, facial paralysis and dysarthria. Tomography of the brain showed ischemic lesions. The echocardiogram suggested the presence of valvular vegetations. He was admitted to hospital with the diagnosis of Borrelia burgdorferi endocarditis, and underwent cardiac surgery with valve replacement. Due to infection of the prosthetic valve and leaking, he had a second surgery a month later. Despite referral to psychology and physical rehabilitation, the patient continues to suffer from numerous deficits, in complex cognitive function. Discussion: Endocarditis may present with subtle clinical manifestations, including dermatological, bone, joint, neurological, cardiac, and systemic signs. There are few case reports of Borrelia burgdorferi endocarditis. The diagnosis is challenging. It involves diagnostic tests that are not readily available to the family physician, requiring referral to secondary care. This tests the competence of the family physician as the patient’s advocate.
Keywords: Endocarditis; Stroke; Family Physician